2010
DOI: 10.1186/1749-8104-5-6
|View full text |Cite
|
Sign up to set email alerts
|

Nav2 is necessary for cranial nerve development and blood pressure regulation

Abstract: BackgroundAll-trans retinoic acid (atRA) is required for nervous system development, including the developing hindbrain region. Neuron navigator 2 (Nav2) was first identified as an atRA-responsive gene in human neuroblastoma cells (retinoic acid-induced in neuroblastoma 1, Rainb1), and is required for atRA-mediated neurite outgrowth. In this paper, we explore the importance of Nav2 in nervous system development and function in vivo.ResultsNav2 hypomorphic homozygous mutants show decreased survival starting at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…NAV2 is involved in cerebellar and cranial nerve development, as well as in blood pressure regulation [52,53]. Recently, the NAV2 gene was found to be frequently fused to the WNT pathway gene TCF7L1 in colorectal carcinoma in a study by the Cancer Genome Atlas Network [54].…”
Section: Discussionmentioning
confidence: 99%
“…NAV2 is involved in cerebellar and cranial nerve development, as well as in blood pressure regulation [52,53]. Recently, the NAV2 gene was found to be frequently fused to the WNT pathway gene TCF7L1 in colorectal carcinoma in a study by the Cancer Genome Atlas Network [54].…”
Section: Discussionmentioning
confidence: 99%
“…Neuron navigator 2 ( NAV2 , also known as r etinoic- a cid i nduced in n euro b lastoma-1; RAINB1, POMFIL1, HELAD1, unc53H2 ) functions in neurite outgrowth and axonal elongation in organisms ranging from Caenorhabditis elegans ( C. elegans ) to humans [14]. NAV2 was initially discovered as a gene induced by all- trans retinoic acid (atRA) in human neuroblastoma (SH-SY5Y) cells [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested that this gene plays an important role in cellular growth, migration, neuronal elongation and nervous system development (Coy et al, 2002;, Ishiguro et al, 2002; Maes et al, 2002; Merrill et al, 2002; Peeters et al, 2004; Clagett-Dame et al, 2006; McNeill et al, 2010; Marzinke et al, 2013). Furthermore, the NAV2 gene may be associated with episodic memory scores in AD (Yan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism for the role of NAV2 in AD still remains unclear. An animal model has shown that the NAV2 gene plays an important role in shaping the development of the mammalian nervous system and is involved in blood pressure regulation (McNeill et al, 2010). One human study revealed that the AD associated SNP rs2702663 in the present study was previously associated with both plaque presence and area in Dominican families (Dong et al, 2012), implicating that NAV2 polymorphisms may be involved in the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation